Supercritical fluid electrodeposition, structural and electrical characterisation of tellurium nanowires. Issue 65 (21st August 2017) - Bartlett, Philip N.; Cook, David A.; Hasan, Mahboba M.; Hector, Andrew L.; Marks, Sam; Naik, Jay; Reid, Gillian; Sloan, Jeremy; Smith, David C.; Spencer, Joe; Webber, Zondy
Abstract : Crystalline sub 20 nm semiconducting nanowires have been electrodeposited from a supercritical fluid for the first time. Abstract : Supercritical fluid electrodeposition (SCFED) was employed for rapid deposition (2.5 μm min −1 ) of tellurium nanowires (TeNW) of nominal size range 13 nm to 55 nm diameter and tens of micrometers in length. Anodic aluminium oxide (AAO) membranes were used as hard templates for the electrodeposition by evaporation of platinum or gold onto one face to form the electrode. TeNWs were characterised both in situ and after removal of the AAO template by XRD, Raman spectroscopy and electron microscopy. The nanowires were crystalline with a strong preferred orientation in all cases. The typical 〈001〉 growth direction was always observed for samples produced using platinum coated membranes; however for the gold coated membranes, a chemical reaction between the tellurium(iv ) precursor and the gold led to atypical 〈110〉 growth. Transistor devices were fabricated from individual TeNWs and their electrical properties characterised.